Field Service Optimization for Manufacturing and Automotive: Advanced Design Strategies for Distributed Work Order Orchestration and Technician Routing - Rajesh , Prabu Vincent De Paul (International Journal of Computing and Engineering, 2025)
Abstract Production facilities and vehicle repair centers wrestle with machinery growing more elaborate daily, making old-school fix-it strategies mediocre. The blueprint presented here organizes scattered repair tasks and worker assignments using innovative methods that transform emergency fixes into planned maintenance activities. Blending artificial intelligence with cloud platforms and instant data exchange lets companies juggle multiple operational pieces at once. Smart territory mapping morphs with demand fluctuations as algorithms pair worker skills to specific repair needs. Mobile tools keep repair crews connected to headquarters, maintaining workflow even when cell towers disappear. Parts distribution networks balance stockpile expenses against component availability, getting critical pieces to workers precisely when required. Digital pathways link phone alerts, electronic mail, software programs, and online dashboards, ensuring clients stay updated throughout repairs. Combined platforms create networks that gain intelligence after every completed job. Factory equipment sends distress signals before breakdowns halt production lines. Car service centers manage electric drivetrains and computer-controlled safety systems across scattered locations. Online systems deliver big-business capabilities to neighborhood garages lacking huge tech budgets. Replacing fixed maintenance calendars with dynamic equipment tracking prolongs machinery lifespan while cutting operational overhead. Businesses adopting unified platforms achieve remarkable operational advances, converting repair divisions from money pits into strategic assets that secure market leadership.